200 Comparison of daily rotation and slow rotational grazing on ewe performance, parasite infestation, and soil. (29th July 2019) - Bradley, Kailey; Boyd, Brooke; Garrison, Lindsay; Higgins, Morgan; Newton, Robert; Vega, Miranda; Gates, Roger; Daniel, Jay
Abstract: Impact of grazing method on ewe performance, parasite infestation, and soil was examined using mature, non-lactating ewes divided into slow rotation (SR; n = 20) or daily rotation (DR; n = 20) groups. Pastures previously grazed by sheep were divided and soil sampled. Temporary electric fence provided daily pasture allocation for DR. Ewes had been adapted to temporary electric fence for two weeks. Both DR and SR were moved to new pasture at the same time. Ewes were weighed and fecal egg counts were conducted biweekly. On alternate weeks, ewes were body condition scored (BCS), FAMACHA scored, and dewormed if FAMACHA score was 4 or greater. After 10 weeks of grazing (June 1-August 10, 2018), final ewe weights and soil samples were collected. Body condition score, FAMACHA, fecal egg count, body weight, and soil test results were tested for effect of grazing group, date, and group by date interaction using procedures for repeated measures with JMP software (version 10, SAS Inst. Inc., Cary, NC). The FAMACHA scores were greatest on July 6 (P < 0.0001). BCS were greater on June 8 and 22 than July 6 and August 3 (P < 0.0001). Ewes were heaviest on June 1 and 15, lightest on July 27 and August 10 (P < 0.0001), and DR ewes were lighter than SR ewes on July 27 and August 10 (P < 0.0001). No effect of treatment, date, or treatment by date interaction on fecal egg count (P > 0.23) was detected. Soil organic matter decreased over the study (P = 0.0024), but organic matter change was less in DR than SR (P = 0.0092). DR did not influence parasitism, but may enhance soil organic matter.